DISORDERS/DIFFERENCES OF SEX DEVELOPMENT: TERTIARY CENTRE EXPERIENCE - Mijatovic , Snjezana; Milenkovic , Tatjana; Sedlecki , Katarina; Kojovic, Vladimir; Ilic, Predrag; Martic, Jelena; Mitrovic, Katarina; Todorovic , Sladjana; Marjanovic , Marko; Toncev , Jovana; Panic-Zaric, Sanja; Vukovic, Rade (HEALTH CARE, 2021)
Introduction/aim: Disorders of sex development (DSD) comprise a heterogeneous group of congenital conditions with a difference between chromosomal, gonadal sex and the appearance of the external genitalia. The frequency of DSD is 1: 4500-5500 newborns per year. Congenital adrenal hyperplasia (CAH) due to the deficiency of the 21-hydroxylase enzyme is one of the most common and best-known causes of DSD. Other forms of CAH, as well as other causes of DSD, occur with significantly lower individual frequencies and are thus more challenging to diagnose and treat. The aim of the study was to analyse the etiology and clinical characteristics of DSD, as well as changes in the diagnostic and therapeutic approach to DSD in the tertiary center during the previous 13 years. Methods: The study was conducted in the form of a retrospective cohort study which included all patients investigated for DSD at the Department of Endocrinology of Mother and Child Health Care Institute of Serbia "Dr Vukan Cupic" during the period from December 2007 until November 2020. Children with DSD caused by CAH due to 21-hydroxylase deficiency were not included in this study. Results: The study included a total of 31 children with DSD: 24 children (77%) had 46XY DSD, 3 (10%) had 46XX DSD, and 4 children (13%) had chromosomal DSD. A definitive diagnosis of specific etiology has been made in 25 children (81%), and the most common etiology of DSD was gonadal dysgenesis (55%), followed by the androgen insensitivity syndrome (10%) and atypical forms of CAH (7%). During the period 2 (2016-2020) more children with DSD (n = 18) were examined compared to the period 1 (2007-2015) and the specific etiological diagnosis was established in a larger number of children with DSD (89%) compared to the period 1 (69%). Also, during period 2 (2016-2020) genital surgery was performed in a significantly lesser number of children (11%) and at a later age (average age 6.8 years) than in period 1 (64%, average age 4.8 years; p <0.05). Conclusion: During the latter period (2016-2020), there has been an increase in the number of investigated children as well as the percentage of DSD with established specific etiology. Also, the diagnosis is increasingly being made on the basis of genetic analysis, and genitoplasty is performed in a decreasing number of children and at a later age. A holistic and multidisciplinary approach is required for the evaluation treatment of children with DSD.